Endogenous biosynthesis of n-3 long-chain PUFA in Atlantic salmon. Issue 10 (5th March 2019) - Mock, Thomas S.; Francis, David S.; Jago, Matthew K.; Glencross, Brett D.; Smullen, Richard P.; Turchini, Giovanni M.
Abstract: A more efficient utilisation of marine-derived sources of dietary n -3 long-chain PUFA ( n -3 LC PUFA) in cultured Atlantic salmon ( Salmo salar L.) could be achieved by nutritional strategies that maximise endogenous n -3 LC PUFA synthesis. The objective of the present study was to quantify the extent of n -3 LC PUFA biosynthesis and the resultant effect on fillet nutritional quality in large fish. Four diets were manufactured, providing altered levels of dietary n -3 substrate, namely, 18 : 3 n -3, and end products, namely, 20 : 5 n -3 and 22 : 6 n -3. After 283 d of feeding, fish grew in excess of 3000 g and no differences in growth performance or biometrical parameters were recorded. An analysis of fatty acid composition and in vivo metabolism revealed that endogenous production of n -3 LC PUFA in fish fed a diet containing no added fish oil resulted in fillet levels of n -3 LC PUFA comparable with fish fed a diet with added fish oil. However, this result was not consistent among all treatments. Another major finding of this study was the presence of abundant dietary n -3 substrate, with the addition of dietary n -3 end product (i.e. fish oil) served to increase final fillet levels of n -3 LC PUFA. Specifically, preferential β -oxidation of dietary C18 n -3 PUFA resulted in conservation of n -3 LC PUFA from catabolism. Ultimately, this study highlights the potential for endogenous synthesis of n -3 LC PUFA to, partially, support a substantial reduction in the amount of dietary fish oil in diets for Atlantic salmon reared in seawater.